Quantum Chemistry Insight into the Interactions Between Deep Eutectic Solvents and SO2 - Mert Atilhan (1272906) (2019)
A systematic research work on the rational design of task specific Deep Eutectic Solvents (DES) has been carried out via density functional theory (DFT) in order to increase knowledge on the key interaction parameters related to efficient SO2 capture by DES at a molecular level. A total of 11 different DES structures, for which high SO2 affinity and solubility is expected, have been selected in this work. SO2 interactions in selected DES were investigated in detail through DFT simulations and this work has generated a valuable set of information about required factors at the molecular level to provide high SO2 solubility in DES, which is crucial for enhancing the current efficiency of the SO2 capture process and replacing the current state of the art with environmentally friendly solvents and eventually implementing these materials in the chemical industry. Results that were obtained from DFT calculations were used to deduce the details of the type and the intensity of the interaction between DES and SO2 molecules at various interaction sites as well as to quantify short-range interactions by using various methods such as quantum theory of atoms in a molecule (QTAIM), electrostatic potentials (ESP) and reduced density gradients (RDG). Systematic research on the molecular interaction characterization between DES structures and SO2 molecule increases our knowledge on the rational design of task-specific DES. Other Information Published in: Molecules License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/molecules24162963